Economic analysis of evolution/devolution of electronic devices functionality - Esipov A. S. (Interactive science, 2017)
the researcher of this article has presented the analysis of evolution/devolution of electronic devices functionality as well as the analysis of the current situation at the computers and mobile devices market, and some thoughts about new products. Is a newer device better? Are corporations producing really new devices or they are only the improvement of old ones.
Keywords: компьютер; экономика; маркетинг; продажи; капитализм; marketing; economics; computer; смартфон; запланированное устаревание; эволюция электроники; закон Мура; planned obsolescence; smartphone; the evolution of electronics; Moore's law; capitalism